Hypoglycemia unawareness in type 1 diabetes patients using intermittent continuous glucose monitoring: Identification of risk factors and glycemic patterns. Issue 6 (June 2022) - Vieira, Inês H.; Barros, Luísa M.; Baptista, Carla F.; Melo, Miguel; Rodrigues, Dírcea M.; Paiva, Isabel M.
Abstract: Background: Hypoglycemia unawareness designates failure to detect eminent hypoglycemia. Clarke's questionnaire is one of the most used systems to evaluate this problem. Aims: To relate Clarke's questionnaire (QQ) results with continuous glucose monitoring data. Methods: Application of the questionnaire in a sample of type 1 diabetes mellitus (T1DM) patients using intermittent continuous glucose monitoring (iCGM). Results: 111 T1DM patients were evaluated, 56.8% female, mean age 35.0 ± 12.4 years and mean disease duration 18.8 ± 10.5 years. According to CQ, 13.5% had unawareness, 76.6% awareness and 9.9% indeterminate awareness to hypoglycemia. Those with unawareness had longer disease duration (25.1 ± 10.4 vs 18.2 ± 10.3 for awareness and 14.9 ± 9.9 for indeterminate awareness, p = 0.047), more time below range (10.3 ± 4.9% vs 6.3 ± 5.1 and 6.3 ± 4.8; p = 0.009) and higher mean duration of hypoglycemia (131.7 ± 38.6 vs 116.6 ± 49.6 and 131.7 ± 38.6; p = 0.008). In multivariate analysis, mean duration of hypoglycemia was an independent predictor of CQ results. In a receiver operating curve (AUC 0.746; p = 0.004) a mean duration of hypoglycemia ≥106.5 min showed 84.6% sensitivity/64.4% specificity for unawareness. Conclusions: Our sample had a significative prevalence of hypoglycemia unawareness which increased with longer diabetes duration. iCGM data can be indicative of this problem, with a mean hypoglycemia duration ≥106.5 min being suggestive, albeit unspecific. Highlights: Hypoglycemia unawareness is common in type 1 diabetes mellitus patients and increases the risk of severe hypoglycemia. Questionnaires provide a useful tool to detect this problem, with Clarke's questionnaire being one of the most widely used. Continuous glucose monitoring data can also alert to this problem. Patients with hypoglycemia unawareness have longer time below range and longer duration of hypoglycemia. Hypoglycemia unawareness exclusively during sleep can be difficult to detect in self-awareness questionnaires.